Associations between psychiatric disorders, COVID-19 testing probability and COVID-19 testing results: findings from a population-based study - Dennis van der Meer; Justo Pinzón-Espinosa; Bochao D. Lin; Joeri K. Tijdink; Christiaan H. Vinkers; Sinan Guloksuz; Jurjen J. Luykx (BJPsych Open, 2020)
Background Many psychiatrists are worried their patients, at increased risk for COVID-19 complications, are precluded from receiving appropriate testing. There is a lack of epidemiological data on the associations between psychiatric disorders and COVID-19 testing rates and testing outcomes.